Aftermath of Banking Crises : Effectson Real and Monetary Variables - Gupta, Poonam (IMF Working Papers; Working Paper, 2000)
In this paper a simple optimizing model is developed to analyze the implications of a banking crisis. Banks are incorporated by assuming that they intermediate funds between firms and households. It is shown that when depositors perceive the quality of deposits to have deteriorated, they switch from deposits to cash. Because of the higher cost of liquidity, consumption, M2 and the M2 multiplier decline, interest rates on deposits and loans increase and output contracts. The findings of the paper match the key stylized facts of banking crises.